Cancer cells govern miR‐2909 exosomal recruitment through its 3′‐end post‐transcriptional modification. (21st February 2018) - Wani, Sameena; Kaul, Deepak
Abstract : It is widely believed that selective packaging of nucleic acids, especially microRNAs, into exosomes secreted by the cancer cells not only ensures their growth and survival but also helps in the escape from immune surveillance. Keeping in view the fact that human cellular miR‐2909 has emerged to regulate genes involved in oncogenesis and immunity, the present study was addressed to reveal the nature of miR‐2909 expression within cancer cells of different tissue origin and its incorporation into exosomes secreted by these cells. Post‐transcriptional modification, especially 3′‐end adenylation and uridylation of miR‐2909, exerts opposing effects that may contribute to direct its sorting into exosomes secreted by cancer cells. Our study also revealed that selective partitioning of adenosine kinase, between cancer cells and their secreted exosomes, may be responsible for the nature of post‐transcriptional modification of miR‐2909 observed within these cells.